Exploring the “15-minute city” and near working in Milan using mobile phone data - Mariotti, Ilaria; Giavarini, Viviana; Rossi, Federica; Akhavan, Mina (TeMA - Journal of Land Use, Mobility and Environment, 2022)
This paper investigates the changes in neighbourhood attractiveness during the Covid-19 pandemic (2020) compared to the year before in 2019 in the city of Milan. Central neighbourhoods recorded a drop in users from -63% to -47%, while the peripheral areas showed a relatively steady presence during the day. Indeed, remote working and the fear of public transport led to rethinking commuting and re-value working close to home. Semi-peripheral and peripheral neighbourhoods have gained a renewed role in attracting remote workers, and coworking spaces represent a valuable alternative for those willing to improve work-life balance through near working. Within this context, the paper aims to:(i) measure the presence of remote workers at the neighbourhood level; (ii) explore the accessibility to coworking spaces within 15 minutes of walking and cycling distance; (iii) focus on three peripheral neighbourhoods which show the lowest number of city users loss, do not host CSs, and present different levels of essential services and access to subway stations. The three cases are explored to understand whether they are considered feasible locations for hosting a neighbourhood coworking space. The change of the city users’ presence in the Milan neighbourhoods in 2019-2020 is analysed using «TIM Big Data – Data Visual Insight», which includes the presence and mobility of the TIM mobile network’s users.